Efeitos da aplicação de remediação térmica sobre a microbiota do solo em áreas contaminadas por compostos orgânicos - Horimouti, Tatiana Satiko Terada [UNIFESP] (2019)
Given the industrialization and urban expansion in brazil, directly linked to a disorganization of the physical space and a set of environmentally unsustainable processes such as land use and occupation without regard to the parameters of environmental protection, the recognition of contaminated areas grows annually, compromising several social and environmental aspects. With the evolution of this complex issue, several techniques for the remediation of these areas were developed, such as thermal remediation, which consists in the application of heat to remove contaminants present in the soil. This work aimed to understand how thermal remediation affects the microbiology of typically brazilian soils, being tested two types of soil: without contamination and with contamination. For this, microcosms were elaborated with the soils, submitted to different temperatures (350º, 270º, 100º and 60ºc) and incubated at room temperature for up to 90 days, followed by quantification by the micro drop technique and dapi staining. Results showed that in a controlled environment, at temperatures of 350ºc and 270ºc, soil sterilization occurred, at 100ºc and 60ºc the growth of cells in petri dish was conditioned to the time the soil was subjected to heating and the physicochemical properties that were altered at these temperatures, which are also factors that influence the recolonization of the soil after the impact of the heating. From the results obtained, it was concluded that in a controlled environment, high temperature thermal remediation sterilizes the soil and at milder temperatures limits the growth of microorganisms. In temperatures above 270oc and after 1 hour of heating, microbial density was not recovered after 60 days of incubation. Further studies are needed to understand how the diversity of this community is affected by heating.